Can Body Fat Percentage, Body Mass Index, and Specific Field Tests Explain Throwing Ball Velocity in Team Handball Players? - Souhail Hermassi; Lawrence D. Hayes; René Schwesig (Applied Sciences, 2021)
This study examined the physical fitness, anthropometry, and throwing velocity of normal weight and overweight male team handball players. Twenty-five players from the Qatar handball first professional league participated. The anthropometry and physical performance—yo-yo intermittent recovery test, jumping ability (squat and countermovement jumps (SJ and CMJ)), T-half test for change-of-direction (COD) ability, sprint tests (15 and 30 m), and 3 kg medicine ball overhead throw—was measured. The handball-throwing velocity was measured using a three-step running shot and a jump shot. Only the CMJ (p = 0.016, ηp2 = 0.227) was different between the normal and overweight subjects. Two-step linear regression analysis using body height and body mass (step 1) and percentage body fat (%BF) (step 2) predictors showed an increase in the explained variance by adding %BF. The largest r2 change was calculated for COD (0.53). The predictive ability was observed for CMJ (step 1: r2 = 0.18, step 2: r2 = 0.22) and SJ (step 1: r2 = 0.05, step 2: r2 = 0.09). With the exception of the sprint parameters (β-coefficient 15 m sprint: −0.07; β-coefficient 30 m sprint: −0.06) and COD (β-coefficient: −0.09), a lower %BF was associated with greater performance in all parameters. %BF seems to be important for predicting sprint and agility performance.